Building back better: granular energy technologies in green recovery funding programs - Wilson, C; De Stercke, S; Zimm, C (Elsevier, 2023)
Granular energy technologies with smaller unit sizes and costs deploy faster, create more jobs, and distribute benefits more widely than lumpy large-scale alternatives. These characteristics of granularity align with the aims of fiscal stimulus in response to COVID-19. We analyze the technological granularity of 93 green recovery funding programs in France, Germany, South Korea, and the UK that target £72.9 billion for low-carbon energy technologies and infrastructures across five emissions-intensive sectors. We find that South Korea’s “New Deal” program is the most technologically granular with strong weighting toward distributed renewables, smart technologies, electric vehicle charge points, and other relatively low unit cost technologies that are quick to deploy. The UK has the least granular portfolio, concentrating large amounts of public money on small numbers of mega-scale energy projects with high implementation risks. We demonstrate how technological granularity has multiple desirable characteristics of green recovery: jobs, speed, and distributed benefits.